2000
DOI: 10.1086/315349
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte–Endothelial Cell Coculture Enhances Infection of Endothelial Cells withChlamydia pneumoniae

Abstract: To determine the mechanism(s) by which Chlamydia pneumoniae homes to and establishes persistent infection in atheromatous lesions, the effect of the interaction of monocytes/macrophages (U937 cells) with human umbilical vein endothelial cells (HUVECs) and transformed human arterial endothelial cells (HMEC-1s) on the susceptibility of endothelial cells to infection with C. pneumoniae was investigated. Infection was enhanced 4.7-fold (HUVECs) and 4.4-fold (HMEC-1s) after coculture at monocyte-to-endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…As discussed above, the human monocyte-like cell U937 was able to amplify chlamydial replication in smooth muscle and epithelial cells (26,28). In our experiments, the GR1 Ϫ /CD11b ϩ cell population, which may include monocytes/macrophages, also weakly amplified chlamydial replication, although the differences were not statistically significant.…”
Section: Figure 5 Depletion Of Gr1supporting
confidence: 44%
See 1 more Smart Citation
“…As discussed above, the human monocyte-like cell U937 was able to amplify chlamydial replication in smooth muscle and epithelial cells (26,28). In our experiments, the GR1 Ϫ /CD11b ϩ cell population, which may include monocytes/macrophages, also weakly amplified chlamydial replication, although the differences were not statistically significant.…”
Section: Figure 5 Depletion Of Gr1supporting
confidence: 44%
“…A similar function has been reported for the monocyte-like cell U937. Thus, coculture of U937 cells with human endothelial cells enhanced the infection of the latter cells by C. pneumoniae (26). Subsequently, it was suggested that the infectivity-enhancing factor is identical with human insulin-like growth factor 2 (27).…”
Section: Figure 5 Depletion Of Gr1mentioning
confidence: 99%
“…Pathology studies have detected the organism within atherosclerotic lesions but not in adjacent normal tissue by immunohistochemistry, PCR, and electron microscopy (19), and the pathogen has been isolated from atherosclerotic lesions and propagated in vitro (4,19,27). Cell biology studies have suggested that the organism can be detected in circulating leukocytes, has the capacity to infect all atheroma cell types (13,28,34), and can induce the expression of inflammatory cytokines, procoagulants, matrix metalloproteinase, and adhesion molecules (8,9,12). Animal model studies have shown that C. pneumoniae can cause arterial inflammation in normolipidemic mice and rabbits and initiate lesion development or contribute to exacerbation of lesions in rabbits or mice, respectively (29,33).…”
mentioning
confidence: 99%
“…Previous studies from our laboratory have shown that Chlamydia trachomatis MOMP is glycosylated and contains N-linked high-mannose-type oligosaccharides (16). Also, the mannose residues in the glycan have been shown to mediate internalization, as C. trachomatis can utilize the mannose receptor to enter and establish productive infection in mouse macrophages, while C. pneumoniae appears to use a receptors(s) other than the mannose receptor (15).Recently, a monocyte-derived soluble factor, insulin-like growth factor 2 (IGF2), was shown to enhance infection of endothelial cells by C. pneumoniae, but not C. trachomatis, suggesting involvement of an IGF2 receptor in C. pneumoniae infection (18,19). The IGF2 receptor also binds mannose 6-phosphate (M6P) and is called the M6P/IGF2 receptor (23).…”
mentioning
confidence: 99%
“…Recently, a monocyte-derived soluble factor, insulin-like growth factor 2 (IGF2), was shown to enhance infection of endothelial cells by C. pneumoniae, but not C. trachomatis, suggesting involvement of an IGF2 receptor in C. pneumoniae infection (18,19). The IGF2 receptor also binds mannose 6-phosphate (M6P) and is called the M6P/IGF2 receptor (23).…”
mentioning
confidence: 99%